Gods and heroes of old Japan - Pasteur, Violet M. (K. Paul, Trench, Trübner and co., ltd., 1906)
Prologue: The way of the gods.--The story of the making of the mirror.--The story of the finding of the sword.--The story of Fire-shine and Fire-fade.--The story of Yamoto-dake the hero.--The story of the good emperor.--The story of the perfect knight. pt. I-II.--The story of the loyal samurai.